Qualitative research for quantitative researchers - Kara, Helen (SAGE Publications, 2022)
Approaching qualitative research for the first time and unsure how to get started? Whether you have years of quantitative experience or have previously only taken a quantitative-focused course, this book captures what you need to know and how to leverage your existing research skillset to jump into effective qualitative or mixed methods research. Getting you up to speed on the specifics of qualitative research, the book shows how it complements quantitative research and how to draw on and hone your existing skills to conduct impactful research. It covers the whole research process, from explaining what theories are for and planning your research design through collecting and working with your data to developing good practice in research reporting and dissemination. The book also: Showcases the value of qualitative research, helping you understand its relevance, credibility and validity. Grapples with how to decolonise your methodology and thinking, do research in an ethical and inclusive way, and debias your data. Challenges you to rethink how you conduct research and choose the most appropriate methods for your project. Giving you a fuller understanding of methods and methodologies to benefit your work regardless of the approach you choose, this book encourages you to discover the joy of qualitative research.--